2016
DOI: 10.1002/admi.201500684
|View full text |Cite
|
Sign up to set email alerts
|

Interfacially Engineered Sandwich‐Like rGO/Carbon Microspheres/rGO Composite as an Efficient and Durable Microwave Absorber

Abstract: EM pollution, because they can convert the EM energy into thermal energy or dissipate the EM waves through interference. [ 4,5 ] Among many kinds of microwave absorbers, carbon materials are always the most attractive candidates due to their tunable properties, relative low density, abundant resource, easy preparation, and low cost. Various carbon materials, e.g., carbon nanotubes (CNTs), carbon nanofi bers (CNF), carbon nanocoils, and mesoporous carbon, have been utilized to construct highly effective microwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 137 publications
(67 citation statements)
references
References 64 publications
2
65
0
Order By: Relevance
“…Microwave absorbers (MAs) are widely used in a variety of fields ranging from military, aerospace to consumer electronics, for eliminating unwanted electromagnetic (EM) radiation or scattering so as to improve the performance or reduce the EM pollution . With the extensive investigation in the past decades, various types of MAs have been developed and widely applied.…”
Section: Introductionmentioning
confidence: 99%
“…Microwave absorbers (MAs) are widely used in a variety of fields ranging from military, aerospace to consumer electronics, for eliminating unwanted electromagnetic (EM) radiation or scattering so as to improve the performance or reduce the EM pollution . With the extensive investigation in the past decades, various types of MAs have been developed and widely applied.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, according to Figure c, the dielectric loss of the Fe 3 O 4 /MWCNTs composite makes a major contribution as the loss tangent of Fe 3 O 4 /MWCNTs is higher than that of Fe 3 O 4 NPs. Besides magnetic loss also influences the EM wave absorption . Magnetic tangent loss (tan δ µ = µ″ nne ) shows a similar trend with imaginary part of permeability versus frequency, as shown in Figure d.…”
Section: Resultsmentioning
confidence: 54%
“…Liu and co‐workers also demonstrated that the 3D graphene networks benefit from the advantage of more effective electrical loss in terms of dissipating induced currents at very low densities. [20b] Recently, monolithic 3D graphene‐based composite foams prepared by Gao and co‐workers exhibited ultralow percolation thresholds of 0.006 vol% . The skeleton‐assisted bicontinuous microstructure endowed the composite foam with a conductive graphene framework and a mechanically robust sponge‐like skeleton of melamine.…”
Section: Graphene‐based Materials For Microwave Absorptionmentioning
confidence: 99%
“…Graphene hybrid absorbers possess relatively larger qualified absorption bandwidths compared with those of EAMs based on RGO, but the graphene/magnetic hybrid absorbers have the disadvantages of poor temperature and corrosion tolerance. Monolithic 3D graphene‐based foams demonstrate wider qualified absorption bandwidths than those of other kinds of graphene‐based absorbers,[7h,11a,15a,20b,55] indicating the superiority of these highly porous and hierarchical structures of graphene. Nevertheless, their mechanical strengths are still a problem for their practical application.…”
Section: Graphene‐based Materials For Microwave Absorptionmentioning
confidence: 99%
See 1 more Smart Citation